Electronic exchange of the freight transportation market of the Russian Federation ("Journal "U". Economy. Management. Finance.", 2024)
In Russia, the transport logistics situation is quite complicated due to the rather vast expanses, both the state and many different companies are trying to find effective methods to optimize and improve the delivery of goods to the final buyer. Today, there are many solutions, and many are also looking for new ways to significantly influence the freight market, constantly improving the situation and contributing to the development of infrastructure. It is safe to say that in recent decades the situation has improved significantly in many ways, and the system is constantly being improved. In this article, we will talk about the significant contribution to the commercial market of freight transportation by road in Russia, which combines many effective solutions.
Keywords: cargo transportation; electronic exchanges; cargo transportation exchange; online cargo transportation platform